Racjonalność a organizacja i informatyzacja rachunkowości - Gil, Waldemar (Rationality and Organization and Informatics' Accountancy, 2005)
Contemporary accountancy systems in economic units is based on a technique of electronic transformation of data. The implementation of information technology solutions is conditioned by many factors. The computer system in turn must reflect the information system. It is important that the procedures of putting into practice were based on the best methods, giving positive results. Informatics' accountancy of an economic unit should take place in a logical manner, smart and well-founded, and at the same time should be able to supplement and order the organization of accountancy in the subject.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 96-106